Rewarding Provider Performance to Enable a Healthy Start to Life : Evidence from Argentina's Plan Nacer - Gertler, Paul; Giovagnoli, Paula; Martinez, Sebastian (World Bank, Washington, DC, 2014)
Argentina's Plan Nacer provides insurance for maternal and child health care to uninsured families. The program allocates funding to provinces based on enrollment of beneficiaries and adds performance incentives based on indicators of the use and quality of maternal and child health care services and health outcomes. The provinces use these resources to pay health facilities to provide maternal and child health care services to beneficiaries. This paper analyzes the impact of Plan Nacer on birth outcomes. The analysis uses data from the universe of birth records in seven Argentine provinces for 2004 to 2008 and exploits the geographic phasing in of Plan Nacer over time. The paper finds that the program increases the use and quality of prenatal care as measured by the number of visits and the probability of receiving a tetanus vaccine. Beneficiaries' probability of low birth-weight is estimated to be reduced by 19 percent. Beneficiaries have a 74 percent lower chance of in-hospital neonatal mortality in larger facilities and approximately half this reduction comes from preventing low birth weight and half from better postnatal care. The analysis finds that the cost of saving a disability-adjusted life year through the program was $814, which is highly cost-effective compared with Argentina's $6,075 gross domestic product per capita over this period. Although there are small negative spillover effects on prenatal care utilization of non-beneficiary populations in clinics covered by Plan Nacer, no spillover is found on their birth outcomes.